2016
DOI: 10.21273/hortsci.51.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genotype and Isolate on Expression of Dollar Spot in Seashore Paspalum

Abstract: Seashore paspalum (Paspalum vaginatum Swartz) is a warm-season turfgrass species primarily used on golf courses and athletic fields, and is often impacted by the disease dollar spot caused by Sclerotinia homoeocarpa F.T. Bennett. Dollar spot is the most common and economically important turfgrass disease in North America, and current management of this disease relies heavily on frequent fungicide applications. An alternate management strategy is hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…This study, conducted under more controlled environmental conditions in growth room and greenhouse settings, although with only two isolates, corroborates the results of field trials conducted by Steketee et al (2016) in that we also found no interactive effect between seashore paspalum genotypes and dollar spot isolates. Chakraborty et al (2006) found no interaction between genotypes of creeping bentgrass ( Agrostis stolonifera L.) and dollar spot isolates.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This study, conducted under more controlled environmental conditions in growth room and greenhouse settings, although with only two isolates, corroborates the results of field trials conducted by Steketee et al (2016) in that we also found no interactive effect between seashore paspalum genotypes and dollar spot isolates. Chakraborty et al (2006) found no interaction between genotypes of creeping bentgrass ( Agrostis stolonifera L.) and dollar spot isolates.…”
Section: Resultssupporting
confidence: 91%
“…This study, conducted under more controlled environmental conditions in growth room and greenhouse settings, although with only two isolates, corroborates the results of field trials conducted by Steketee et al (2016) in that we also found no interactive effect between seashore…”
Section: Inoculation and Data Collectionsupporting
confidence: 88%
See 1 more Smart Citation
“…To our knowledge, these UDB cultivars have not been evaluated for resistance to foliar diseases; however, another study demonstrated an increased leaf spot susceptibility of FloraDwarf compared with TifEagle and Tifdwarf cultivars (Brecht et al, 2007). Results of this study, together with previous studies, indicate that variation in disease resistance likely exists among modern UDB cultivars (Bonos et al, 2003; Brecht et al, 2007; Bonos and Weibel, 2008; Tomaso‐Peterson and Young, 2010; Steketee et al, 2016). Consequently, a thorough disease resistance assessment among UDB cultivars is warranted.…”
Section: Discussionsupporting
confidence: 72%
“…Host resistant cultivar selection has been demonstrated in many host‐pathogen interactions; however, the usefulness of this approach is dependent on the availability of host resistance to a particular disease (Couch, 1995; Brecht et al, 2007; Bonos and Weibel, 2008; Tomaso‐Peterson and Young, 2010; Watschke et al, 2013). Research of host resistance to turfgrass diseases among UDB cultivars is limited; however, studies in other cool‐ and warm‐season turfgrass species provide a basis for such investigations (Bonos et al, 2003; Brecht et al, 2007; Bonos and Weibel, 2008; Tomaso‐Peterson and Young, 2010; Steketee et al, 2016).…”
mentioning
confidence: 99%